2017
DOI: 10.1038/s41598-017-15172-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the FA pathway combined with CHK1 inhibitor hypersensitize lung cancer cells to gemcitabine

Abstract: The combination of platinum and gemcitabine is one of the standard regimens in the treatment of advanced lung squamous carcinoma (LSC). Resistance to gemcitabine is main barrier to the successful treatment of LSC. In this study, we showed that suppression of the Fanconi anemia (FA) pathway increased the sensitivity of two LSC cell lines SK-MES-1 and KLN205 to gemcitabine. Moreover, we found that the CHK1 pathway and the FA pathway are functionally compensatory in the repair of DNA damage in the LSC cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The KLN 205 cell line has been applied in around 100 published research studies. While morphologically it seems non-negotiable that KLN 205 in culture appears similar to SCC cells [12][13][14]24,25] , they have been applied as models for lung cancer in general [15][16][17][18][19][20][21][22] , metastatic lung cancer cells [26] and even non-small cell lung cancer [23] . Surprisingly, they have even worked as a model for tongue cancer [27] and subcutaneous SCC [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KLN 205 cell line has been applied in around 100 published research studies. While morphologically it seems non-negotiable that KLN 205 in culture appears similar to SCC cells [12][13][14]24,25] , they have been applied as models for lung cancer in general [15][16][17][18][19][20][21][22] , metastatic lung cancer cells [26] and even non-small cell lung cancer [23] . Surprisingly, they have even worked as a model for tongue cancer [27] and subcutaneous SCC [28] .…”
Section: Discussionmentioning
confidence: 99%
“…• SCC [12][13][14] • Lung cancer [15][16][17][18][19][20][21][22] • Non-small cell lung cancer [23] • L-SCC [24,25] • Lung-metastatic tumour cells [26] • Tongue cancer [27] • Subcutaneous SCC [28] It was shown previously that a comprehensive molecular cytogenetic characterisation of murine tumour cell lines can define the cancer subtype to which they belong because the cytogenomic profile of chromosomal imbalances is typically specific to a certain tumour type [6] . Thus, the karyotype, a comprehensive map of chromosomal imbalances, and an in silico translation of these results to the human genome were performed here for the KLN 205 cell line to possibly determine to which human cancer type it is most similar.…”
Section: Introductionmentioning
confidence: 99%
“…FA pathway is responsible for repairing DNA crosslinks and double strand breaks and maintaining chromosomal stability 37 . It was demonstrated that FA pathway activation occurs during DNA replication or upon DNA damage induced by carcinogens in cigarette smoke 38 or by DNA cross linking agents, such as the chemotherapeutic agents gemcitabine and cisplatin 39 .…”
Section: Discussionmentioning
confidence: 99%
“…A siRNA-based screening identified ATM as synthetically lethal in Fanconi anemia deficient cell lines, indicating that this gene could be targeted concomitantly with a FA pathway inhibitor [185]. Moreover, combination of CHK1 inhibitor with FANCD2 depletion hyper-sensitizes lung cancer cells to gemcitabine [124]. Several molecules that inhibit specific components of the FA pathway have been identified acting at different levels; for instance, phenylbutyrate sensitizes head and neck cancer cells to cisplatin by reducing the expression of FANCS [179], curcumin acts on the mono-ubiquitination step of FANCD2 sensitizing ovarian and breast tumor cell lines to cisplatin and glioma cell lines to alkylating agents, also MLN4924 suppresses FANCD2 mono-ubiquitination sensitizing cells to DNA ICLs agents [180][181][182] (Table 6).…”
Section: Mln4924mentioning
confidence: 99%